Reproductive Characteristics and Induced Breeding in Heterobranchus longifilis - Jojo Subagja; Rudhy Gustiano (Fakultas Biologi | Universitas Jenderal Soedirman, 2005)
Two experiments were conducted in the IRD-Gamet Laboratory, Montpellier, France. The first was to evaluate the recovery of Heterobranchus longifilis female gonad after induced ovulation, under tropical condition. Oocyte diameter was used as indicator of the recovery rate following by induced breeding, hatching rate and abnormality of larvae. The results showed that the recovery was about 28 to 35 days after ovulation. The second was carried out to improve the milt production by hormone treatments. Volume of intratesticular sperm and the number of spermatozoa were observed. The results indicated that the treatmens did not prove any significant difference.